2023
DOI: 10.3390/life13091909
|View full text |Cite
|
Sign up to set email alerts
|

Posture of Healthy Subjects Modulated by Transcutaneous Spinal Cord Stimulation

Natalia Shamantseva,
Olga Timofeeva,
Alisa Gvozdeva
et al.

Abstract: Transcutaneous electrical stimulation of the spinal cord is used to restore locomotion and body weight support in patients with severe motor disorders. We studied the effects of this non-invasive stimulation on postural control in healthy subjects. Stimulation at the L1–L2 vertebrae was performed to activate the extensor muscles of the lower limbs. Because postural regulation depends on the cognitive style, the effects of the stimulation were analyzed separately in field-dependent (FD) and field-independent (F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The electrodes were placed on the skin -cathodes over the spinal motor centers, at the level of C3-C5, T11-T12 or L1-L2 vertebrae, and anodes over the iliac crests or clavicles [1]. Many studies with healthy subjects have shown that tSCS modulates spinal neuronal networks, manifested by changes in locomotion and posture [14][15][16][17].…”
Section: Transcutaneous Spinal Cord Stimulationmentioning
confidence: 99%
“…The electrodes were placed on the skin -cathodes over the spinal motor centers, at the level of C3-C5, T11-T12 or L1-L2 vertebrae, and anodes over the iliac crests or clavicles [1]. Many studies with healthy subjects have shown that tSCS modulates spinal neuronal networks, manifested by changes in locomotion and posture [14][15][16][17].…”
Section: Transcutaneous Spinal Cord Stimulationmentioning
confidence: 99%
“…Subsequent studies have validated this concept. Many studies with healthy subjects have shown that tSCS modulates spinal neuronal networks, manifested by changes in locomotion and posture [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%